Violation Information and Student Achievement with a Website-Based System at the School of Insan Cendekia Mandiri Boarding School - Muhammad Lutfi Idham (Procedia of Engineering and Life Science, 2022)
Education is a very important thing to develop the potential of students to become human beings who believe and fear God Almighty, and become human beings who are beneficial to the homeland and nation. Over time, education and technology can collaborate to facilitate the teaching and learning process. However, in classical educational institutions or what we know as Islamic boarding schools, they still rarely use technology to improve their system and education. Therefore, this is one of the reasons that encourage researchers to build a website-based information system on student violations and achievements at the Insan Cendekia Mandiri boarding school boarding school which aims to assist ustadz and ustazah in seeing the development of their students and making it easier for them to take on policy. This system uses the HTML, PHP and SQL database programming languages and this research method uses the WDLC (Web Development Life Cycle) system which is often used to build and develop websites, in this method there is a website development cycle, namely planning, analysis, design, implementation, finishing and maintenance.